2004
DOI: 10.1097/00005537-200410000-00031
|View full text |Cite
|
Sign up to set email alerts
|

Stress as a Trigger of Attacks in Menière's Disease. A Case‐Crossover Study

Abstract: Being exposed to emotional stress increases the risk of getting an attack of Menière's disease during the next hour, and the hazard period is possibly extended up to 3 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 10 publications
(14 reference statements)
1
38
0
Order By: Relevance
“…Although we cannot rule out the possibility that Ménière's disease is a hydrops complex of 11.7% 88.3% -n = Number of audiogram pairs; recovery = shift to a milder category; worsening = shift to a more severe category. [23][24][25][26][27] . We suspect that keys to understanding the disease may be hidden in the variability of prognosis, age distribution of patients, differing prevalence between the sexes, lack of environmental factors, and failure to fi nd topical causes in the inner ear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we cannot rule out the possibility that Ménière's disease is a hydrops complex of 11.7% 88.3% -n = Number of audiogram pairs; recovery = shift to a milder category; worsening = shift to a more severe category. [23][24][25][26][27] . We suspect that keys to understanding the disease may be hidden in the variability of prognosis, age distribution of patients, differing prevalence between the sexes, lack of environmental factors, and failure to fi nd topical causes in the inner ear.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been suggested that Ménière's disease is a typical stress-induced or psychosomatic disease, there have been only a few studies investigating causative factors arising out of the daily lives of patients [23][24][25][26][27] . To identify factors of daily life inducing Ménière's disease, we have conducted several studies.…”
Section: Introductionmentioning
confidence: 99%
“…A time-series analysis of stress and vertigo expression did not support the role of stress as a precursor of symptoms in Menière's disease (Andersson et al, 1997). On the contrary, Sö derman et al did find that emotional stress increased the risk of getting a vertigo attack (Sö derman et al, 2004).…”
Section: Sumariomentioning
confidence: 93%
“…Demographic features, familial MD history, accompanying other systemic chronic disease history, and bilaterality of the disease findings were similar to those of other studies [36][37][38][39][40][41] . It has been reported that the emotional stress is the most powerful attack indicator [31,[41][42][43][44] . Our finding was the same.…”
Section: Discussionmentioning
confidence: 99%